Electric Field Simulation and Effect of Different Solvent Ratios on the Performance of Single Electrospun PVDF/PEI Composite Film - Jin-gang Jiang; Zhao Wang; Hong-wei Duan; Jing-qiang Liu; Xiao-wei Guo (Advances in Materials Science and Engineering)
On the basis of the finite element calculation theory of electric field, the electric field distribution in a representative electrospinning device is computed. The electric field structure of a needle-plate type electrospinning device was simulated by means of ANSYS software. And the vector distribution of the nozzle on the spinneret pipe was got. For the purpose of the analysis on the influence of different solvent ratios on the performance of a single electrospun PVDF/PEI composite film, polyvinylidene fluoride and polyetherimide with a mass ratio of 8/2 were dissolved in a mixed solvent. The mixed solvent is composed of N,N-dimethylformamide and tetrahydrofuran, added in different proportions. Through the electrostatic spinning technology, PVDF/PEI composite fiber membranes were prepared. Using scanning electron microscopy (SEM), X-ray diffraction (XRD), differential scanning calorimetry (DSC), and mechanical properties testing, the effects of tetrahydrofuran on the composite microstructure, crystallinity, and mechanical properties of the PVDF/PEI composite fiber membranes are discussed.